(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This article intends to stimulate the debate about the need to reread the fundamental right of access to justice, given the scenario of mass judicialization and hegemony of jurisdiction in the resolution of conflicts.